Combined Lifestyle Behaviors and the Incidence of Common Cancer Types in the Norwegian Women and Cancer Study (NOWAC) - Chen,Sairah LF; Braaten,Tonje; Borch,Kristin B; Ferrari,Pietro; Sandanger,Torkjel M; Nøst,Therese H (Clinical Epidemiology, 2021)
Sairah LF Chen,1 Tonje Braaten,1 Kristin B Borch,1 Pietro Ferrari,2 Torkjel M Sandanger,1 Therese H Nøst1 1Department of Community Medicine, UiT The Arctic University of Norway, Tromsø, Norway; 2Nutrition and Metabolism Branch, International Agency for Research on Cancer, World Health Organization, Lyon, FranceCorrespondence: Sairah LF ChenDepartment of Community Medicine, UiT The Arctic University of Norway, Hansine Hansens veg 18, Tromsø, 9019, NorwayTel +47 77644786Email sairah.chen@uit.noIntroduction: Only a small number of studies have examined the impact of combined lifestyle behaviors on cancer incidence, and never in a Norwegian population.Purpose: To examine linear and nonlinear associations of combined lifestyle factors, assessed through a healthy lifestyle index (HLI), with the incidence of postmenopausal breast, colorectal, lung, postmenopausal endometrial, postmenopausal ovarian, pancreatic, and kidney cancer among women in Norway.Methods: This prospective study included 96,869 women enrolled in the Norwegian Women and Cancer (NOWAC) cohort. Baseline information on lifestyle factors was collected between 1996 and 2004. The HLI was constructed from five lifestyle factors: physical activity level, body mass index, smoking, alcohol consumption, and diet. Each factor contributed 0 to 4 points to the HLI score, which ranged from 0 to 20, with higher scores representing a healthier lifestyle. Multiple imputation was used to handle missing data. Cox proportional hazard regression models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI). Restricted cubic splines were used to examine nonlinearity in the associations.Results: The HRs for a one-point increment on the HLI score were 0.97 (95% CI: 0.96– 0.98) for postmenopausal breast cancer, 0.98 (0.96– 1.00) for colorectal cancer, 0.86 (0.84– 0.87) for lung cancer, 0.93 (0.91– 0.95) for postmenopausal endometrial cancer, 0.99 (0.96– 1.02) for postmenopausal ovarian cancer, 0.92 (0.89– 0.95) for pancreatic cancer, and ...